Nitrogen uptake regime and phytoplankton community structure in the Atlantic and Indian sectors of the Southern Ocean - Semeneh, M.; Dehairs, Frank; Elskens, Marc; Baumann, M.E.M.; Kopczynska, E.E.; Lancelot, Christiane; Goeyens, Léo (1998)
Phytoplankton nitrogen uptake is studied in relation to the biomass and structure of phytoplankton community in the Atlantic and Indian sectors of the Southern Ocean. Two scenarios of seasonal evolution of uptake regime and phytoplankton community structure are described. The first scenario includes the Marginal Ice Zone areas of the Weddell Sea and adjacent areas where a predominantly nitrate based, diatom dominated assemblage, thriving in a stable water column at the beginning of the season was transformed into a mainly ammonium based, flagellate dominated assemblage, towards the end of the season. The change in phytoplankton community structure was caused by selective grazing by large grazers and reduced stability of the water column and the shift in uptake regime was due to increased ammonium availability and changes in community structure. In the second scenario, in the Coastal and Continental Shelf Zone (CCSZ) and Open Oceanic Zone (OOZ) of the Indian sector, a shift in uptake regime occurred without a big change in phytoplankton community structure. These areas were sampled late in the growth season and were characterized by prolonged water column stability, less grazing pressure on large diatoms and high ammonium availability. Diatoms dominated the assemblage and about 80% phytoplankton biomass was on the > 10 μm size fraction. Unlike the first scenario, diatoms were largely based on ammonium. Thus, in areas of persistent water column stability and less selective grazing pressure, a shift in uptake regime can occur without change in community structure. The dominance of diatoms under regenerated production provides a physiological evidence for the excess net removal of silicate over nitrate occurring in certain provinces of the Southern Ocean. info:eu-repo/semantics/published